Pileflebite: Uma Revis#xE3;o Sistem#xE1;tica (Global Journal of Medical Research, 2022)
Introduction: Pylephlebitis is characterized as a portal vein thrombophlebitis, which occurs as a complication of intra-abdominal infections. It is more related to diverticulitis and appendicitis, being a rare complication with a high rate of morbidity and mortality. Objective: To carry out a systematic review of pylephlebitis, taking into account its clinical, diagnostic and treatment aspects. Methodology: The work consists of a systematic review, analyzing 20 articles on pylephlebitis, from 2013 to 2021. Discussion: Pylephlebitis has nonspecific manifestations, making diagnosis and early treatment difficult. The management of the disease consists of using computed tomography, which has been shown to be the best diagnostic method, and early antibiotic therapy. The use of anticoagulation in the treatment is still much discussed.